2016
DOI: 10.4049/jimmunol.1502478
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidins Have Direct Antiviral Activity against Respiratory Syncytial Virus In Vitro and Protective Function In Vivo in Mice and Humans

Abstract: Respiratory syncytial virus (RSV) is a leading cause of respiratory tract infection in infants, causing significant morbidity and mortality. No vaccine or specific, effective treatment is currently available. A more complete understanding of the key components of effective host response to RSV and novel preventative and therapeutic interventions are urgently required. Cathelicidins are host defense peptides, expressed in the inflamed lung, with key microbicidal and modulatory roles in innate host defense again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 57 publications
5
87
1
2
Order By: Relevance
“…It is known that 1,25(OH) 2 D 3 enhances antimicrobial activity via interaction with VDR to up-regulate the synthesis of antimicrobial peptides such as cathelicidin and β-defensin [55,56]. Cathelicidin is produced by neutrophils, monocytes, and macrophages and has broad antimicrobial activity against bacteria, as well as viruses, such as respiratory syncytial virus (RSV) [57,58]. Moreover, under subclinical inflammatory conditions, vitamin D may be less able to control inflammatory responses in otherwise healthy individuals [59].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that 1,25(OH) 2 D 3 enhances antimicrobial activity via interaction with VDR to up-regulate the synthesis of antimicrobial peptides such as cathelicidin and β-defensin [55,56]. Cathelicidin is produced by neutrophils, monocytes, and macrophages and has broad antimicrobial activity against bacteria, as well as viruses, such as respiratory syncytial virus (RSV) [57,58]. Moreover, under subclinical inflammatory conditions, vitamin D may be less able to control inflammatory responses in otherwise healthy individuals [59].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in Bpifa1 levels after IAV infection in our study suggests that early expression may be necessary in host defense and its reduction may be associated with damage to the epithelia. Human LL-37 was recently shown to have direct antiviral properties against respiratory syncytial virus and mouse CAMP reduced viral infectivity (Currie et al, 2016). While we did not use CAMP as a therapeutic in this study, we noted increased Camp expression in response to IAV that remained elevated throughout the infection perhaps indicative of a role for CAMP in antiviral responses to IAV.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we showed trends toward increased baseline production of inflammatory cytokines TNF-␣ and CCL5/RANTES, hinting that chronic airway inflammation could contribute to defective antiviral responses upon infection observed in some patients. A previous study in airway epithelial cell cultures demonstrated that proinflammatory cytokine exposure impaired epithelial expression of cathelicidin (29), an antimicrobial peptide that has antibacterial and antiviral properties (4,7). Exposure to proinflammatory cytokines can induce persistent epigenetic changes that modify innate immune responses.…”
Section: L901mentioning
confidence: 99%